19/40 as a fraction and decimal it is 0.475
Gemma was hiking for 2 1/2 a hour for 3 hours so u have to multiply 2.5 by 3 and that gonna equal 7.5 so u leave that alone and come back to it later so u get 11 3/8 minus 7.5 and it gonna equal 3 7/8 and I hope that helped you
No, Joe and Grace don’t have enough together because 11/10 is only 1.1 and 3/4 is .75 and u add that together u get 1.85 which is less 2.
Grace needs 12 cups of sugar to make the cookies because 1 cups of sugar makes 6 cookies and each person is getting 3 that’s only enough for 2 people , so multiple every by 12 to get 24 people, 12 cups of sugar, and 72 cookies .
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
![AB = \sqrt{ ({3 - ( - 2)})^{2} + ({4 - 0})^{2} } \\](https://tex.z-dn.net/?f=AB%20%3D%20%20%5Csqrt%7B%20%28%7B3%20-%20%28%20-%202%29%7D%29%5E%7B2%7D%20%2B%20%20%28%7B4%20-%200%7D%29%5E%7B2%7D%20%20%7D%20%20%5C%5C%20)
![AB = \sqrt{ ({3 + 2})^{2} + {4}^{2} }](https://tex.z-dn.net/?f=AB%20%3D%20%20%5Csqrt%7B%20%28%7B3%20%2B%202%7D%29%5E%7B2%7D%20%2B%20%20%7B4%7D%5E%7B2%7D%20%20%7D%20)
![AB = \sqrt{ {5}^{2} + {4}^{2} }](https://tex.z-dn.net/?f=AB%20%3D%20%20%5Csqrt%7B%20%7B5%7D%5E%7B2%7D%20%2B%20%20%7B4%7D%5E%7B2%7D%20%20%7D%20)
![AB = \sqrt{25 + 16}](https://tex.z-dn.net/?f=AB%20%3D%20%5Csqrt%7B25%20%2B%2016%7D%20)
![AB = \sqrt{41}](https://tex.z-dn.net/?f=AB%20%3D%20%5Csqrt%7B41%7D%20)
![AB = 6.403](https://tex.z-dn.net/?f=AB%20%3D%206.403)
![AB = 6.4](https://tex.z-dn.net/?f=AB%20%3D%206.4)
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
Answer:
![y=-\frac{x}{6} -1](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7Bx%7D%7B6%7D%20-1)
Step-by-step explanation:
Hi there!
We are given the following equation:
x+6y=-6
And we want to convert it into slope-intercept form
Slope-intercept form is known as y=mx+b, where m is the slope and b is the y intercept
The equation is currently in standard form, which is ax+by=c, where a, b, and c are integer coefficients
Notice how in standard form, both the terms that contain x and y are on one side, but in slope-intercept form, y is by itself on one side
So essentially, in order to convert from standard form to slope-intercept form, we need to solve for y
Here is our equation again:
x+6y=-6
Start by subtracting x from both sides
x+6y=-6
-x -x
_______________
6y=-x-6
Now divide both sides by 6
![y=-\frac{x}{6} -\frac{6}{6}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7Bx%7D%7B6%7D%20-%5Cfrac%7B6%7D%7B6%7D)
We can simplify the fractions to become:
![y=-\frac{x}{6} -1](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7Bx%7D%7B6%7D%20-1)
Hope this helps!
See more on converting from standard to slope-intercept form here: brainly.com/question/26579052